La Extracción sólido-líquido de oleorresinas de páprika (Capsicum annuum, L) - Terry Calderóna, Víctor Manuel (2014)
In the present investigation, the proximal composition of paprika was determined (Capsicum annuum, L); the balance of materials in the operations of drying, milling and extraction of its oleoresin; also, the physicochemical values of the oleoresin. An equipment of Soxhlet extraction of 500 mL, with hexane. Each cycle of extraction corresponded to a volume of 300 ml and with five cycles of extraction a concentration of oleoresin of 98% was obtained, with a yield of the operation of 8.2 g of oleoresin/100 g of paprika.